Transformational leadership and organizational citizenship behavior: Mediating role of affective commitment and work engagement of hotel employees in Indonesia - Jufrizen; Salman Farisi; Muslih; Maya Sari (Problems and Perspectives in Management, 2023)
Employees who voluntarily conduct work that surpasses the criteria allocated to them to help the company achieve its goals exhibit organizational citizenship behavior. This study aims to examine the mediation role of affective commitment and work engagement on the influence of transformational leadership on organizational citizenship behavior. This study used survey methodology. Two hundred frontline staff working over a year in several star-rated hotels in Medan, Indonesia, are used as samples. Data were collected using a Likert scale questionnaire and analyzed using structural equation modeling-part least squares with SmartPLS 4.0 software. The findings show that transformational leadership, affective commitment, and work engagement affect organizational citizenship behavior (p < 0.05). Next, transformational leadership affects affective commitment (p < 0.05) and work engagement (p < 0.05), and transformational leadership affects organizational citizenship behavior through affective commitment (p < 0.05) and work engagement (p < 0.05). The findings of this study recommend that hotel management should use a transformational leadership style when filling managerial positions. In addition, the study results have implications for businesses in terms of creating arrangements that encourage employee engagement and affective commitment, enabling workers to volunteer their time, energy, and ideas to serve their co-workers and the company. This paper helps to develop human resources to maintain the sustainability of hotel industry in Medan, Indonesia. AcknowledgmentThis study is supported by all levels of management at Universitas Muhammadiyah Sumatera Utara for funding Fundamental research in 2022 and thanks also to the ranks of the Institute of Research and Community Service (LPPM) Universitas Muhammadiyah Sumatera Utara.